The German version of the brief affective neuroscience personality scales including a LUST scale (BANPS–GL) - Fuchshuber, Jürgen; Prandstätter, Theresa; Andres, Deborah; Roithmeier, Lisa; Schmautz, Beate; Freund, Anton; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Human Neuroscience, 2023)
Objectives This study presents the German version of the Brief Affective Neuroscience Personality Scales (BANPS), which includes an additional subscale for the dimension LUST. The BANPS represents a shortened version of the Affective Neuroscience Personality Scales (ANPS), a self–report instrument to assess individual dispositions toward primary emotional systems as proposed by Jaak Panksepp. Methods In a large sample (N = 926), the reliability and various facets of validity of the German translation of the BANPS were examined together with the newly included LUST scale. The BANPS–GL was related to the Big Five Inventory (BFI) and Sexual Sensation Seeking Scale (SSSS) and analyzed via confirmatory factor analysis (CFA). Results Overall, the BANPS–GL exhibited reliabilities ranging from McDonald’s ω = 0.70 (CARE) to α = 0.86 (SADNESS) and plausible correlations with external criteria. For CFA a correlated 7–factor model demonstrated good fit [TLI = 0.95; RMSEA = 0.04 (90% CI: 0.04, 0.05); SRMR = 0.06]. A similar fit was demonstrated for a 2–higher–factor model [TLI = 0.93; RMSEA = 0.05 (90% CI: 0.05, 0.06); SRMR = 0.07]. Conclusion In broad agreement with the results of the original English version, the BANPS–GL showed good reliability and acceptable factorial validity, and overall improved the psychometric properties of the original long form. Finally, the inclusion of the dimension LUST allows for a complete coverage of the primary emotion dispositions as originally conceptualized by Panksepp.